A Meta-Analysis of Environmental Impacts of Agri-Environmental Policies in the European Union - Katrin Oltmer; Peter Nijkamp; Raymond Florax; Floor Brouwer (Tinbergen Institute, 2000)
This paper applies an ANOVA-type of meta-analysis to the evaluation of agri-environmental policy in theEuropean Union. Meta-analysis is concerned with the statistical analysis of previous research results, andhas become an established technique in the medical and natural science. The paper investigates whetherspecific conditions, under which agri-environmental measures are applied, have an effect on thebehaviour of farmers with respect to three indicators, N-fertiliser, livestock density and area of grassland.The results indicate that agri-environmental policy intervention has a positive effect on the behaviour offarmers participating in agri-environmental programmes. The average premium per hectare and theabsolute value of N-fertiliser, livestock density and area of grassland appear to have a significantinfluence on the behaviour of these farmers.
Keywords: 330; EU-Staaten; Landwirtschaft; EU-Umweltpolitik